The Family Function and Exercise Behavior of Chinese College Students: A Moderated Mediation Model of Exercise Value Cognition and Only-Child Status - Wu, Ming; Wu, Pei-Yao; Yang, Jian; Li, Xin (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the mediating role of exercise value cognition between family function and exercise behavior and the moderating role of only-child status. A questionnaire survey was conducted of 504 Chinese college students by using Family function scale, Exercise value cognition scale and Exercise behavior scale. The analysis yielded four main findings. (1) There are significant differences between only child and non-only child for negative exercise behavior and family function. The only-child group has a higher average family function score and a lower average negative exercise score. (2) Exercise behavior and four of its dimensions – exercise autonomy, attention control, exercise planning, and situational induction – are each significantly positively correlated with family function and exercise value cognition. (3) Family function is a significantly positive predictor of exercise behavior, both directly and through exercise value cognition, which plays a partial mediating role. (4) Only-child status significantly moderates the mediating effect of exercise value cognition in the link between family function and exercise behavior. The inter-group differences mainly manifest in the influence of family function on exercise behavior and the influence of exercise value cognition on exercise behavior. In the only-child subsample, exercise value cognition plays a complete mediating role. The results of the current study demonstrated the important role that family function and exercise value cognition played in promoting the exercise behavior of college students. These findings have important implications for exercise behavior in adolescents by maintaining sound communication between family members and developing a healthy lifestyle or value cognition.